PROCEDURAL FAIRNESS AS INTERVENING VARIABLE BETWEEN VOICE AND PERFORMANCE EVALUATION FORMALITY ON TRUST - Prasetya, Jeremia Allan; Wijayanti, Dian (Jurnal Aplikasi Manajemen, 2018)
This study aims to test the hypothesis developed by Hartmann and Slapnicar (2009). Thatis to examine the influence of subordinate participation and performance evaluation formality in the process of performance evaluation of trust through the perception of procedural fairness. This research uses a survey method, which is data retrieval through a questionnaire. Subjects in this study are all staffs in one of the University of Malang who has met the criteria. The test used Partial Least Square (PLS). Results showed that the participation of subordinates was not able to improve the perception of procedural fairness directly, but can increase trust. While, the formalities of performance evaluation, directly able to improve the perception of procedural fairness, but can not increase trust. However, if tested indirectly performance evaluation formality can increase trust through the perception of procedural fairness, whereas subordinate participation cannot improve. Conclusion, this study supports the hypothesis developed by Hartmann and Slapnicar (2009), but there are some unsupported hypotheses because of the difference of the research object, where each research object has different evaluation system according to organizational objectives.